Hypertensive disorders in pregnancy: current evidence, short-term and long-term outcomes - Hanzhyi, I. Yu.; Vizir, V. A.; Demidenko, O. V.; Bohuslavska, N. Yu.; Kuchkovskyi, O. M.; Ганжий, Ірина Юріївна; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович; Богуславська, Н. Ю.; Кучковський, Олег Миколайович (Запорізький державний медико-фармацевтичний університет, 2025)
Aim: to analyze current scientific literature on the prevalence short-term and long-term outcomes of hypertensive disorders during pregnancy, with a particular focus on preeclampsia, and to identify promising strategies for prevention and postpartum follow-up in women affected by these complications. Materials and methods. A literature search was conducted in PubMed, Scopus, Web of Science, Medline, and UpToDate using the keywords: hypertensive disorders in pregnancy, gestational hypertension, preeclampsia, eclampsia, long-term outcomes, short-term outcomes, maternal cardiovascular risk, offspring, neurodevelopment, postpartum follow-up, cardiovascular prevention. Publications from 2020–2025 were prioritized. The review included systematic reviews, meta-analyses, cohort studies, and clinical guidelines. After exclusions, 70 publications meeting the criteria for relevance, evidence level, and clinical significance were analysed. Results. The review summarizes the main clinical forms of hypertensive disorders during pregnancy – gestational hypertension, preeclampsia, and eclampsia – and highlights an upward trend in prevalence, particularly for gestational hypertension. The impact of the COVID-19 pandemic on incidence patterns is noted. Reported long-term maternal consequences – including cardiovascular, metabolic, and neurological disorders – as well as for their children, who may experience neurodevelopmental and psycho-emotional disturbances. Мета роботи – проаналізувати відомості сучасної наукової літератури щодо поширеності короткострокових і віддалених наслідків гіпертензивних розладів у вагітних, зокрема прееклампсії, а також визначити перспективні напрями профілактики та післяпологового спостереження. Матеріали і методи. Пошук джерел здійснено у базах PubMed, Scopus, Web of Science, Medline та UpToDate за ключовими словами: hypertensive disorders in pregnancy, gestational hypertension, preeclampsia, eclampsia, long-term outcomes, short-term outcomes, maternal cardiovascular risk, offspring, neurodevelopment, postpartum follow-up, cardiovascular prevention. До аналізу включено 70 публікацій (2020–2025 рр.), серед них – систематичні огляди, метааналізи, когортні дослідження та клінічні рекомендації. Результати. Розглянуто основні форми гіпертензивної патології під час вагітності, зокрема гестаційну гіпертензію, прееклампсію, еклампсію. В останнє десятиліття встановлено тенденцію до збільшення їхньої поширеності, особливо гестаційної гіпертензії. Окрему увагу приділено впливу пандемії COVID-19 на динаміку гіпертензивних ускладнень. Узагальнено дані про віддалені наслідки для жінок, як-от про підвищення ризику хронічної артеріальної гіпертензії, ішемічної хвороби серця, інсульту, серцевої недостатності, метаболічних і неврологічних розладів. У дітей, народжених від таких вагітностей, встановлено більшу ймовірність виникнення серцево-судинної патології, порушень нейророзвитку та психоемоційного стану.
Гіпертензивні розлади під час вагітності: актуальні дані, короткострокові та віддалені наслідки
Keywords: pregnancy; hypertension; hypertensive disorders in pregnancy; preeclampsia; gestational hypertension; endothelial dysfunction; cardiovascular diseases; long-term outcomes; prevention; COVID-19; postpartum follow-up; literature review; вагітність; гіпертензивні розлади; гіпертензивні розлади у вагітних; прееклампсія; гестаційна гіпертензія; ендотеліальна дисфункція; серцево-судинні захворювання; віддалені наслідки; профілактика; післяпологове спостереження; огляд літератури